Forging Russia's Arctic strategy: actors and decision-making. Issue 1 (2nd January 2019) - Sergunin, Alexander; Konyshev, Valery
ABSTRACT: This study examines how Arctic policies are being made in present-day Russia. More specifically, this paper focuses on the roles and functions of various actors and institutions participating in the decision-making process. Both governmental and non-governmental actors are examined. The effectiveness of the decision-making mechanism is assessed. Major problems in organisation and functioning of this system are identified. The authors conclude that a rather stable decision-making machinery on Arctic policy has been created within the executive branch of the Russian government. The elements of parliamentary control over the decision-making process have been created. An executive-legislative liaison/consultative mechanism has been established and it facilitated the dialogue between the Kremlin and the legislature on Arctic policies. The role of the Russian regional and local governments became more salient in Arctic policy-making. Russia's Arctic regional and local governments develop numerous horizontal/networking-type relations (paradiplomacies) with their foreign partners. Non-governmental actors, such as the Russian business community, human rights, indigenous peoples' and environmental NGOs have got some say in Arctic policy-making. Despite some shortcomings the Russian Arctic policy-making system evolved in a more democratic and efficient way. Transitional period still continues but the grounds for optimistic expectations are quite solid.